Development Of A Meso-Scale Combustor For Liquid Fuel Combustion - Hamzah, Muhammad Al Amien (Universiti Sains Malaysia, 2018)
A meso-scale combustion chamber with liquid fuel combustion and central alumina porous inert media is fabricated which generates higher energy density (per unit volume) or specific energy (per unit mass) compared to lithium battery technology. Porous inert media is known to improve the combustion efficiency with it large surface area of combustion that can generate high thermal energy. With tangential air inlet, a swirl combustion is formed as it can reduce the heat loss of the combustion to the surrounding. The primary aim of this project is to design and develop a swirl combustor which can be used to operate on gasoline and kerosene fuels. The performance aspects of the combustor is discussed in terms of the measured surface and product gas temperature while observing the flame flow during the combustion process. The combustor is fabricated using mild steel as the combustor. Fuel flow rate is adjusted by varying the amount of gasoline added to the kerosene fuel. The air flow rate is varied from 30 to 60 LPM and the temperature measured was between the fuel-air equivalence ratios of 1.3 to 0.6. Besides, the combustion process from 100% kerosene fuel is also simulated using ANSYS Fluent software. The main findings shows that the highest temperature produced with small difference between the surface and gas products temperature by the combustion is at fuel-air equivalence ratio range from 0.9 to 0.7 for all samples of fuel. Plus, the highest temperature recorded at the surface of combustion is around 609°C with 100%y kerosene as the fuel at fuel-air equivalence ratio of 0.77. The swirling flame produces minimal heat loss to the surrounding. Also, as the gasoline content increased in the mixture with kerosene fuel, the fuel flow rate used for the combustion to stabilize also increase. To conclude, the optimal fuel-air equivalence ratio from 0.7 to 0.9 as it produced most stabilize combustion with highest temperature produce and small difference of temperature through the distance of surface temperature. Thus, lean combustion will produced the optimum combustion rather than rich combustion.